CHARACTERIZATION OF SULFATE REDUCING BACTERIA FROM BIOFILM SULFATE REDUCTION AND CU PRECIPITATION BIOREACTOR (BATCH CULTURE). - Tyas Nyonita Punjungsari (JARES (Journal of Academic Research and Sciences), 2017)
The biofilm is a microbial community structure formed on the zeolite surface in a sulfate reduction bioreactor and Cu deposition using a SRB consortium . The biofilm soluble microbial solvent is expected to have the capability in sulfate reduction and Cu deposition. Characterization of isolates is required for the optimization of pure culture . The aim of this study is to isolate and characterize the biofilm sulfate reducing bacteria in the sulfate reduction bioreactor and the precipitation of Cu in Batch Culture by a consortium of Sulfate Reducing Bacteria. The method used in this study cultivation was done by using postgate B medium, isolation was done by diluting biofilm on NaCl salt, bacteria grown on NB and postgate B media, characterization done by morphology and biochemistry. There were 3 isolates of B1 (Metylobacterium ), B3 ( Desulfucoccus ), and B2 ( Desulfobacter ). B3 ( Desulfococcus) has the best ability to reduce sulfate and Cu precipitation.Keywords : Sulfur Reducing Bacteria (SRB), Biofilm, Sulfate, Cu. Received: 26 August, 2017; Accepter: 10 September, 2017